4(y - 7) = 2y - 38
4y - 28 = 2y - 38
4y - 2y = -38 + 28
2y = -10
y = -5
7 . 3
--- × ------
10. . 6
= 21
--------
60
= 7/20
Answer:
The inverse function of h(x) = 3/2*(X-11) is: g(x)= (2/3*X) +11
Step-by-step explanation:
h(x) = Y= 3/2*(X-11)
To find the inverse function, the first step is to exchange the position of the variables with each other. So;
X= 3/2*(Y-11)
Now we need to isolate the variable Y from this equation. The final result will be te inverse function.
X=3/2*(Y-11)
2*X=3*(Y-11)
2/3*X=Y-11
2/3*X +11 = Y
Y= (2/3*X) + 11 (Inverse function)
Perpendicular slope: opposite and reciprocal
-4 opposite and reciprocal = 1/4
Y = 1/4x + b
Plug in point
-3 = 1/4(8) + b
-3 = 2 + b, b = -5
Solution: y = 1/4x - 5